Optimasi Alokasi Produksi untuk Pasar Ekspor Teh Indonesia - Suprihatini, Rohayati (Jurnal Agro Ekonomi, 1999)
EnglishIndonesian tea estate industry has faced the problem of deminishing the profit margin. The aggregate of the profit margin still has an opportunity to be increased such as by optimalizing production allocation for marketing of Indonesian tea. The aims of this research was to find the solution of that optimalization. The approach used was linear programming method. The results show that the optimal solution will increase the profit of national tea industry by US$ 1,826,155, or 16,5 percent of previous profit. The allocation production to Russia, United Kingdom, and Dutch should be increased. On the other hand, the allocation for Pakistan, USA, and domestic market should be decreased. To ease in implementing of this solution, the Marketing Joint Office (MJO) as the only one tea auction in Indonesia should actively invite more buyer candidates from Russia, United Kingdom, and Dutch.IndonesianIndustri perkebunan teh Indonesia masih menghadapi masalah semakin menurunnya marjin keuntungan. Marjin keuntungan agregat masih berpeluang untuk ditingkatkan antara lain melalui upaya optimasi alokasi produksi untuk pasar teh Indonesia. Penelitian ini bertujuan untuk mendapatkan solusi optimal tersebut. Pendekatan yang digunakan adalah pendekatan linear programming. Hasil analisis menunjukkan bahwa dengan optimasi akan meningkatkan keuntungan total industri perkebunan teh nasional sebesar 1.826.155 dollar AS, atau 16,5 persen dari keuntungan semula. Alokasi produksi ke pasar Rusia, Inggris, dan Belanda perlu ditingkatkan. Di lain pihak, alokasi produksi ke pasar Pakistan, Amerika Serikat, dan pasar dalam negeri perlu dikurangi. Agar upaya optimasi tersebut mudah direalisasikan, maka pihak Kantor Pemasaran Bersama (KPB) sebagai lembaga penyelenggara lelang teh satu-satunya di Indonesia perlu aktif mengundang lebih banyak calon pembeli dari Rusia, Inggris, dan Belanda.